Asphalts in road construction - Hunter, Robert N. (Thomas Telford, 2000)
'Asphalts in Road Construction' reflects on the wide range of current practice associated with asphalts and flexible highway construction. It takes into account the major changes in asphalt materials and practice which have affected road design.